2015
DOI: 10.1089/sur.2014.081
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pre-Operative Blood Transfusion and Subcutaneous Fat Thickness as Risk Factors for Surgical Site Infection after Posterior Thoracic Spine Stabilization

Abstract: BACKGROUND Surgical site infections (SSIs) increase morbidity and mortality rates and generate additional cost for the healthcare system. Pre-operative blood transfusion and the subcutaneous fat thickness (SFT) have been described as risk factors for SSI in other surgical areas. The purpose of this study was to assess the impact of pre-operative blood transfusion and the SFT on the occurrence of SSI in posterior thoracic spine surgery. METHODS In total, 244 patients (median age 55 y; 97 female) who underwent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…There are many hypotheses including preoperative anemia, disease severity, deficiencies in nutrition, and immunosuppression related to the transfusion or underlying diseases. 15 Our findings that longer operative time is associated with increased SSI risk after hysterectomy is consistent with a previous study. 5 Finally, we identified Medicaid, a marker of socioeconomic status as a risk factor for SSI after hysterectomy.…”
Section: Analysis Of Observed and Adjusted Ssi Rates After Hysterectomysupporting
confidence: 93%
See 1 more Smart Citation
“…There are many hypotheses including preoperative anemia, disease severity, deficiencies in nutrition, and immunosuppression related to the transfusion or underlying diseases. 15 Our findings that longer operative time is associated with increased SSI risk after hysterectomy is consistent with a previous study. 5 Finally, we identified Medicaid, a marker of socioeconomic status as a risk factor for SSI after hysterectomy.…”
Section: Analysis Of Observed and Adjusted Ssi Rates After Hysterectomysupporting
confidence: 93%
“…5 Finally, we identified Medicaid, a marker of socioeconomic status as a risk factor for SSI after hysterectomy. 15 Individuals qualifying for Medicaid lack financial and possibly social resources compared with those who have private insurance, and this may have an impact on surgical recovery.…”
Section: Analysis Of Observed and Adjusted Ssi Rates After Hysterectomymentioning
confidence: 99%
“…The final article investigating preoperative transfusions found RBC transfusion within 48 hours prior to surgery was independently associated with SSI (OR = 2.7, 95% CI 1.1-6.4, P = .024). 48…”
Section: Resultsmentioning
confidence: 99%
“…Although, the rate of postoperative transfusion in patients in cervical fusion patients is thought to be low, little studies have focused on the effects of transfusion in cervical spine fusion patients. However, multiple studies have shown that higher rates of surgical site infections were associated with receiving blood transfusion [ 5 6 7 ]. In a recent study, the effect of transfusion on primary posterior lumbar surgery was shown to be associated with increased complications [ 8 ].…”
Section: Introductionmentioning
confidence: 99%